The Mountain Caribou in Managed Forests Program: Integrating forestry and habitat management in British Columbia - Stevenson, Susan K.; Child, Kenneth N.; Watts, Glen S.; Terry, Eliot L. (Rangifer, 1991)
Caribou in southeastern and east central British Columbia generally use old-growth forests rather than clearcuts or immature stands. During winter, they subsist on arboreal lichens, which are most abundant in old growth. The Mountain Caribou in Managed Forests program was initiated to adress the question: can forest stands be managed, through silvicultural systems and habitat enhancement techniques, to provide both timber and caribou habitat? The program includes radiotelemetry, habitat capability mapping, habitat management trials, and development of an integrated strategy. The management trials are aimed at maintaining arboreal lichens and other key habitat attributes in managed stands. The strategy development component involves wildlife biologists and foresters in developing and implementing solutions to logging-caribou conflicts.